Numerical Simulation Analysis of the Dynamic Mechanical Property of Concrete Based on 3D Meso-mechanical Model - Fengyan Qin; Jingsong Cheng; Heming Wen; Hongbo Liu (Fracture and Structural Integrity)
The dynamic mechanical property of concrete is very complex and is one of the hot spots in academic research. In this paper, concrete is considered as a three-phase composite composed of cement mortar matrix, coarse aggregate and interfacial transition zone (ITZ) at the mesoscopic level. Numerical simulation of the dynamic response of concrete specimen under impact load is carried out using a 3D meso-mechanical model and combining the dynamic constitutive relation of the concrete. The law of influence of the loading velocity, volume content of the aggregate and particle size of coarse aggregate on the dynamic mechanical properties of concrete are analyzed and discussed. The simulation results show that the damage morphology of concrete under impact loadings is in good agreement with the theoretical analysis and that the peak stress of concrete increases with the impact velocity, indicating there is an obvious strain rate enhancement effect in the concrete. In addition, the peak stress of concrete increases with the growth of the volume content of the coarse aggregate. The simulation results also show that for a constant volume fraction and gradation of coarse aggregate, the peak stress of concrete decreases gradually with the increasing of the particle size of the coarse aggregate.